Acute Complications in Total Wrist Arthroplasty: A National Surgical Quality Improvement Program Review - Eckhoff, Michael D.; Bader, Julia M.; Nesti, Leon J.; Dunn, John C. (Journal of Wrist Surgery, 2020)
Background The study sought to assess the patient-based variables, surgical risk factors, and postoperative conditions associated with readmission after total wrist arthroplasty (TWA).Materials and Methods All patients undergoing TWA were identified from the National Surgical Quality Improvement Program dataset from 2005 to 2016. Patient demographics, medical comorbidities, surgical characteristics, and outcomes were examined to isolate predictors for readmission within 30 days postoperatively.Results A total of 57 patients were identified to have undergone TWA. The average patients were 62.3 (13.8) years old, female (57.7%), and most were treated in the outpatient setting (67.3%). Comorbid conditions included smoking (17.3%), diabetes (15.4%), and chronic steroid therapy (15.4%). No complications were identified in the 30-day postoperative period. There was a trend for increasing utilization of TWA over the years included.Conclusion TWA is a safe procedure with low complication rates in the acute postoperative period. Increasing utilization is likely a result of improved outcomes and cost-effectiveness of TWA.Level of Evidence This is a Level II, prognostic study.
Keywords: arthroplasty; arthrodesis; osteoarthritis; wrist; NSQIP